Properti psikometri Self-Compassion Scale versi Indonesia: Struktur faktor, reliabilitas, dan validitas kriteria - Muttaqin, Darmawan; Yunanto, Taufik Akbar Rizqi; Fitria, Annisa Zaenab Nur; Ramadhanty, Amanda Meuthia; Lempang, Giofanny Filadelfia (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractThe purpose of this study was to examine the psychometric properties of Indonesian version of the Self-Compassion Scale (SCS), a measure self-compassion. Participants were 681 undergraduate students (17-22 years old) at the Faculty of Psychology University of Surabaya. The accidental sampling technique was used as a method of data collection by asking the participants' willingness to be involved in this study by filling in the research informed consent. The confirmatory factor analysis, composite reliability, and correlations were used to examine the factor structure, reliability, and criterion validity. The results found that the six-factor hierarchy model with self-compassion and self-criticism as the main dimensions are the best factor structures and have good internal consistency. The correlations between Indonesian version of the SCS with other measurements proved that Indonesian version of the SCS has a good criterion validity. The result suggests that Indonesian version of the SCS was a valid and reliable measurement tools to measure the self-compassion in Indonesian samples.Keywords: criterion validity; factor structure; reliability; SCS; self-compassion AbstrakPenelitian ini bertujuan untuk menguji properti psikometri dari Self-Compassion Scale (SCS) versi Indonesia yang mengukur self-compassion. Partisipan yang terlibat sebanyak 681 mahasiswa yang berusia 17-22 tahun yang sedang menempuh pendidikan di Fakultas Psikologi Universitas Surabaya. Teknik accidental sampling digunakan sebagai metode pengambilan data dengan meminta kesediaan partisipan untuk terlibat dalam penelitian ini dengan mengisi inform consent penelitian. Analisis konfirmatori faktor, reliabilitas komposit, dan korelasi dengan alat ukur lain digunakan untuk menguji struktur faktor, reliabilitas, validitas kriteria dari SCS versi Indonesia. Hasil analisis konfirmatori faktor menemukan bahwa model hierarki enam faktor dengan self-compassion dan self-criticism sebagai dimensi utama merupakan struktur faktor yang terbaik dan memiliki konsistensi internal yang baik. Adanya korelasi SCS versi Indonesia dengan alat ukur lain membuktikan SCS versi Indonesia memiliki validitas kriteria yang memuaskan. Hasil mengindikasikan bahwa SCS versi Indonesia merupakan alat ukur yang valid dan reliabel untuk mengukur self-compassion pada sampel Indonesia.Kata kunci: reliabilitas; SCS, self-compassion; struktur faktor; validitas kriteria